"Power does not exist, what exists is influence": How mid‐level business and finance staff in private colleges navigate the higher education landscape. Issue 198 (12th September 2022) - Dorantes, Andrew R.; Schiffecker, Sarah Maria; García, Hugo A.
Abstract: In this chapter, the experiences of mid‐level business and finance staff positions in private colleges are explored to illuminate how they engage the campus environment as they help navigate their institutional fiscal vitality through the lens of empowerment theory. Through qualitative interviewers, findings include how they negotiate shared governance with members of the community who have tenure and how they empower those around them.